High-throughput chlorophyll fluorescence screening of Setaria viridis for mutants with altered CO2 compensation points - Coe, Robert A.; Chatterjee, Jolly; Acebron, Kelvin; Dionora, Jacqueline; Mogul, Reychelle; Lin, HsiangChun; Yin, Xiaojia; Bandyopadhyay, Anindya; Sirault, Xavier R. R.; Furbank, Robert T.; Quick, W. Paul (Commonwealth Scientific and Industrial Research Organisation, 2018)
To assist with efforts to engineer a C4 photosynthetic pathway into rice, forward-genetic approaches are being used to identify the genes modulating key C4 traits. Currently, a major challenge is how to screen for a variety of different traits in a high-throughput manner. Here we describe a method for identifying C4 mutant plants with increased CO2 compensation points. This is used as a signature for decreased photosynthetic efficiency associated with a loss of C4 function. By exposing plants to a CO2 concentration close to the CO2 compensation point of a wild-type plant, individuals can be identified from measurements of chlorophyll a fluorescence. We use this method to screen a mutant population of the C4 monocot Setaria viridis (L.)P.Beauv. generated using N-nitroso-N-methylurea (NMU). Mutants were identified at a frequency of 1 per 157 lines screened. Forty-six candidate lines were identified and one line with a heritable homozygous phenotype selected for further characterisation. The CO2 compensation point of this mutant was increased to a value similar to that of C3 rice. Photosynthesis and growth was significantly reduced under ambient conditions. These data indicate that the screen was capable of identifying mutants with decreased photosynthetic efficiency. Characterisation and next-generation sequencing of all the mutants identified in this screen may lead to the discovery of novel genes underpinning C4 photosynthesis. These can be used to engineer a C4 photosynthetic pathway into rice.